2017
DOI: 10.1002/tal.1390
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on the behavior of corrugated steel shear wall subjected to the different angle of trapezoidal plate

Abstract: Summary Studies on corrugated steel shear walls (CSSWs) generally indicate noticeable increase of energy absorption, as well as increasing shear buckling capacity of corrugated plates being more likely rather than the flat plates. In this paper, the effect of variation in the angle of trapezoidal plate on the behavior of CSSWs has extensively been investigated. Three specimens of CSSW with 1 story and single bay in half scale are tested under cyclic load. The observations of experiment do indicate that stress … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 28 publications
3
22
0
Order By: Relevance
“…The impact of crack on the buckling behavior and also the bearing capacity of thin-wall panels must be considered carefully in the design process. [8][9][10][11][12][13] The behavior of cracked plate is studied by Sih and Lee [14] under the influence of tensile and compressive axial loads. They showed that prebuckling capacity was reduced by increasing crack length.…”
Section: Behavior Of the Cracked Platementioning
confidence: 99%
See 1 more Smart Citation
“…The impact of crack on the buckling behavior and also the bearing capacity of thin-wall panels must be considered carefully in the design process. [8][9][10][11][12][13] The behavior of cracked plate is studied by Sih and Lee [14] under the influence of tensile and compressive axial loads. They showed that prebuckling capacity was reduced by increasing crack length.…”
Section: Behavior Of the Cracked Platementioning
confidence: 99%
“…By raising pure shear stress, the panel is buckled under the effect of compressive stresses and undergoes an out‐of‐plane deformation in the diagonal direction. The impact of crack on the buckling behavior and also the bearing capacity of thin‐wall panels must be considered carefully in the design process …”
Section: Introductionmentioning
confidence: 99%
“…Hosseinzadeh et al [9] performed an experimental investigation to the behaviour of corrugated steel plate shear walls with a different angle of trapezoidal plate. The study showed that increasing the corrugation angle results in reducing the stiffness and energy dissipation.…”
Section: Figure 1 Details Of the Geometric Shape Of Cspswmentioning
confidence: 99%
“…To assess the reliability of the FM models, the results of the numerical analysis were compared with the experimental results of Emami et al [5] and Hosseinzadeh et al [9]. The details of the two experimental programs are described below:…”
Section: Figure 2 Fm Modelmentioning
confidence: 99%
“…Zhao et al (2017) and Wang et al(2018) conducted the nonlinear push‐over analyses and cyclic analyses on the flat SPSWs and the corrugated SPSWs. Hosseinzadeh et al (2017) investigated the effect of variation in the angle of trapezoidal plate on the behavior of corrugated SPSWs. It was found that the SPSW deformed greatly in the loading process, and the vertical load bearing capacity of SPSW is weak.…”
Section: Introductionmentioning
confidence: 99%